Does the reliance on nonfinancial measures for performance evaluation enhance managers’ perceptions of procedural fairness? - He, J.; Lau, Chong (Emerald Group Publishing Limited, 2012)
Purpose – The adoption of performance measurement and evaluation systems comprising nonfinancial measures has rendered the investigation of behavioral consequences of such measures an increasingly important research issue. The purpose of this study is to investigate the process by which the use of nonfinancial measures affects employees’ perceptions of procedural fairness. It proposes that the effects of nonfinancial measures on procedural fairness are indirect through the mediating variables of (1) job relevant information and (2) role clarity. Methodology – Data collected from a survey of 276 managers in different functional areas are used to test the models. The data are analyzed using structural equation modeling (Partial Least Square). Findings – Results from structural models indicate that the use of nonfinancial measures has a positive impact on job relevant information, role clarity, and procedural fairness. In addition, the findings suggest that the use of nonfinancial measures is indirectly related to procedural fairness through job relevant information and role clarity. Specifically, the results indicate that the use of nonfinancial measures affects job relevant information. Job relevant information then influences role clarity. Role clarity, in turn, is positively related to procedural fairness.Value of paper – This study provides systematic empirical evidence on how the use of nonfinancial measures for performance measurement and evaluation can affect employee perceptions of procedural fairness. It helps organizations to understand how this process occurs and provides them with some assurance that the adoption of nonfinancial measures may be beneficial particularly through the higher information content of such measures and the consequential enhancement of employee role clarity and perception of fairness. By studying the effects of nonfinancial measures, in isolation, this study also helps to demonstrate to organizations that some of the beneficial effects on employee outcomes found by prior management accounting studies involving a combination of financial and nonfinancial measures may be achievable from the use of nonfinancial measures alone without the need of financial measures. This may assist organizations in designing simpler performance measurement systems.